Digital divide and digital capital in multiethnic Russian society. Issue 2 (2nd April 2020) - Gladkova, Anna; Vartanova, Elena; Ragnedda, Massimo
ABSTRACT: The paper draws linkages between ethnic diversity of the eight federal districts of Russia and their technological development (access and use of ICTs, digital literacy, etc.). We show that although there is no universal correlation between ethnic composition of the regions and the level of their technological advancement, regions where Russians constitute the majority (i.e. Central and Northwestern) more often tend to be the country's leaders in terms of technological development. Following up on this, we use purposive sample of 398 Internet users based in Russia, showing how the level of digital capital of users varies depending on their ethnicity (here we will distinguish between two large groups – Russians and non-Russians, based on self-identification of survey participants) and their place of living. Results of the digital capital study, despite being indicative, show that those belonging to the ethnic majority (in our case Russians) and those living in big cities tend to have a higher level of digital capital. We argue that although ethnicity solely does not define the level of users' digital capital, it is still an important and understudied issue. This is particularly true for big multiethnic societies, such as the Russian society, where digital divide across various groups and regions remains a serious problem.